Odpowiedzi

2009-11-26T15:23:36+01:00
10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10

10y+20+3x-15=x-5
25y+50+3x-15=-10

10y+3x-x=-5-20+15
25y+3x=-10-50+15

10y+2x=-10/ * (-2,5)
25y+3x=-45

-25y-5x=25
25y+3x=-45

-5x+3x=25-45
-2x=-20 / : (-2)
x=10

25y + 3*10=-45
25y + 30 = -45
25y=-45-30
25y=-75 / : 25
y= -3

x=10
y=-3
2009-11-26T15:23:38+01:00
10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10

10y+20+3x-15-x=-5
25y+50+3x-15=-10

10y+2x=-10 /*(-3)
25y+3x=-45 /*2

-30y-6x=-30
50y+6x=-90

20y=-120 /20
y=-6

10y+2x=-10
10*(-6)+2x=-10
-60+2x=-10
2x=50
x=25
2009-11-26T15:26:22+01:00
{10(y+2)+3(x-5)=x-5
{25(y+2)+3(x-5)=-10

{10y+2x=-10 /:2
{25y+3x=-45

{5y+x=-5 /*(-3)
{25y+3x=-45

{-15y-3x=15
+{25y+3x=-45

10y=-30 / :10
y=-3

{5*-3+x=-5
{y=-3

{-15+x=-5
{y=-3

{x=10
{y=-3

Spr:
{10(-3+2)+3(10-5)=10-5
{25(-3+2)+3(10-5)=-10

{10*(-1)+3*5=5
{25*(-1)+3*5=-10

{-10+15=5
{-25+15=-10

{5=5
{-10=-10

L=P